Risk-Adjusted Returns to Education - Judith Delaney (Institute of Labor Economics (IZA), 2019)
This paper looks at the joint impact of labour market risk and selection in to the labour market on returns to education. Accounting for non-employment risk leads to substantial changes in returns while wage risk has little impact. The risk- adjusted returns to both high school and college for males are larger than unadjusted returns. For females, risk leads to an increase in returns to high school but to a decrease in the returns to college while correcting for selection in to employment has large effects for females. The results suggest that failure to account for risk and selection in to employment when calculating returns to education leads to biased estimates.
Keywords: I26; J1; 330; employment; risk; education